THE PURCHASE BEHAVIOUR TOWARDS CONSUMER GOODS DURING ECONOMIC CRISIS – A MIDDLE EASTERN PERSPECTIVE - Andrew Rohanaraj, Thangarasa Tiburtrious (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2023)
The primary purpose of this study is to develop a realistic understanding of the factors that influence consumers’ purchase behaviour towards consumer goods in the middle east region during the economic crisis, by focusing on Oman. This study has used linear regression analysis to develop a clear idea of the factors that influence consumers’ purchase behaviour towards consumer goods during the economic crisis. This study has also used Sobel test, to conduct the mediation analysis. The data was collected using a standard five-point Likert scale-based questionnaire, from a sample of 122 individuals who have recently completed their bachelor’s program in one of the four major Higher Education Institutions (HEIs) in Oman. Unlike the popular belief, this study has found the elements of the marketing mix to not exert significant influence on consumers’ purchase behaviour towards consumer goods during the economic crisis. However, the results found cultural and social factors to exert useful influence on the consumers’ purchase behaviour towards consumer goods. The study recommends that organizations need to focus more on cultural compliance and societal acceptance of their offerings, than focusing on the traditional marketing mix. While helping the organizations manufacturing or marketing consumer goods in the middle east region during the economic crisis, this study would add more value and variety to the available literature. While the findings of this study could also be used by individuals dealing with consumer products in similar markets to redefine their product offerings, by taking the cultural and social issues into consideration, this study could act as a point of reference for future researchers. This study has provided a unique perspective related to the factors that drive consumers’ purchase behaviour towards consumer goods in the middle east region, during the economic crisis. These observations could also be generalized and used in other countries that have similar cultural and social affiliations.